X-Ray Performance of a Customized Large-format Scientific CMOS Detector - Wu, Qinyu; Jia, Zhenqing; Wang, Wenxin; Ling, Zhixing; Zhang, Chen; Zhang, Shuangnan; Yuan, Weimin (Publications of the Astronomical Society of the Pacific, 2022)
In recent years, the performance of Scientific Complementary Metal Oxide Semiconductor (sCMOS) sensors has been improved significantly. Compared with charge-coupled Device sensors, sCMOS sensors have various advantages, making them potentially better devices for optical and X-ray detection, especially in time-domain astronomy. After a series of tests of sCMOS sensors, we proposed a new dedicated high-speed, large-format X-ray detector in 2016 cooperating with Gpixel Inc. This new sCMOS sensor has a physical size of 6 cm × 6 cm, with an array of 4096 × 4096 pixels and a pixel size of 15 μ m. The frame rate is 20.1 fps under current condition and can be boosted to a maximum value around 100 fps. The epitaxial thickness is increased to 10 μ m compared to the previous sCMOS product. We show the results of its first taped-out product in this work. The dark current of this sCMOS is lower than 10 e − pixel −1 s −1 at 20°C, and lower than 0.02 e − pixel −1 s −1 at −30°C. The fixed pattern noise and the readout noise are lower than 5 e − in high-gain situation and show a small increase at low temperature. The energy resolution reaches 180.1 eV (3.1%) at 5.90 keV for single-pixel events and 212.3 eV (3.6%) for all split events. The continuous X-ray spectrum measurement shows that this sensor is able to response to X-ray photons from 500 eV to 37 keV. The excellent performance, as demonstrated from these test results, makes sCMOS sensor an ideal detector for X-ray imaging and spectroscopic application.